Experimental Study On The Effect Of Intake Air Temperature On The Performance Of Spark Ignition Engine Fueled With Hydrogen Peroxide - Roseli, Adnan; Zainol, Sabri Adlan; Abdul Munir, Fudhail; Mohamad Nasir, Asnawi (Asian Research Publishing Network (ARPN), 2018)
The aim of this experiment is to investigate the effect of intake air temperature on the performance of gasoline engine fueled with alternative fuel.The alternative fuel that has been chosen is hydrogen peroxide and it will be blended with gasoline.Some of the characteristics of hydrogen peroxide are it portrays as a strong oxidizing agent however,it is a weak acid when immerse in water.The process of the mixture will be using a device called magnetic stirrer.The specimen used for the test is 5 vol% of hydrogen peroxide + 95 vol% gasoline and 10 vol% hydrogen peroxide + 90 vol% gasoline.Experiment was conducted by using generator engine Precision GX420 single cylinder with 4 strokes.The temperatures chosen for the whole test were 40 °C and 60 °C respectively.The temperatures were controlled by hot air gun where it will be attached at inlet of the engine.Pressure sensor and crank sensor have been installed on the engine to determine pressure,volume and crank angle.The data obtained was recorded and shown in DEWESOFT data acquisition system.